Enterprise resource planning systems selection in the wine industry of the Western Cape : a qualitative case study - Wiid, Hermanus Jacobus (Stellenbosch : Stellenbosch University, 2011)
Thesis (MA (Information Science))--Stellenbosch University, 2011.